Assembly in North West Europe: Collective Concerns for Early Societies?. (1st August 2013) - Semple, Sarah; Sanmark, Alexandra
<x xml:space="preserve">Abstract</x> The archaeological study of assembly practices in the medieval west is often met with scepticism. The reliance on late documentary records and place-names, and the difficulties inherent in defining what actually constituted an 'assembly', are just some of the issues that face researchers. This paper brings together some of the first collated and excavated evidence by the HERA TAP project1, and offers a cross-European perspective, drawing attention to the great variety of systems and types of structure created for the purpose of assembly in the late prehistoric and medieval eras. Selected case studies emphasize the chronological variations in the inception and life-span of assembly places and underline the diverse relationships of designated assembly sites to pre-existing landscapes, resource patterns, and social structures. Connections between the 'architecture' and location of these sites, and their role in the creation, maintenance, and signalling of collective identities are suggested.